Protestant Dissent and the Law: Enforcement and Persecution, 1662–72 - Wykes, David L. ca. 20./21. Jh. (Studies in church history, 2020)
Religious Dissent was shaped by the law. The Act of Uniformity (1662) set out the terms of conformity, and those who could not accept those terms risked prosecution. A great many were convicted under the earlier Elizabethan and Jacobean recusancy statutes, but new laws, such as the Conventicle Acts (1664, 1670) and the Five Mile Act (1665), were also passed. Anthony Fletcher's essay, published in 1984, remains almost the only study of enforcement, in which he argued that the impact of the penal laws on Dissent has been exaggerated because the Conventicle Acts were not systematically enforced. A range of contemporary accounts will be used to suggest that their impact was greater than has been appreciated because of the enforcement of other statutes and the harassment of ejected ministers and their supporters.